Educational Change and Teachers’ Pedagogical Content Knowledge (PCK): Integration for Professional Development - Saxena, Astha; Behari, Alka (INDIAN EDUCATIONAL REVIEW, 2013)
The world is passing through a phase of transformational change. The state, the economy, the society and the ecology are changing in ways that have compelled individuals and nations to confront the aeonian question of what we are and what we aspire to be. Education must facilitate human quest in search of answer to this question. And, if education has to serve this purpose, role of the teachers in this regard can hardly be emphasised. A candle has to burn itself to be able to enlighten the path of others. Likewise, the teachers must brace up not only to the emerging discourse in their respective disciplines but also, and, equally importantly to the ways through which it may be possible for them and their students to construct, deconstruct and reconstruct their worldviews and the paradigms of knowledge. Teacher education is a discipline whose prerogative is to innovate and research upon ways towards betterment in education in its various fields such as curriculum, pedagogy, learning, assessment, etc. One of the variables in teacher education that has been very prominent in teacher education researches has been, Pedagogical Content Knowledge (PCK)***. The underlying contention of the present paper is whether PCK as a construct can in any way prepare our teachers to adapt and deal with the educational change prevailing within their context. For this purpose, a study was carried out with a sample of in-service teachers so as to know about the present notions of educational change amongst our teachers and their own ways of confronting them. The results indicated a mixed response in terms of teachers’ understanding about educational change per se and their ability to deal with the change, if they happen to identify any. The study has its implications for the pre-service as well as in-service teacher education programmes.